Pengaruh Metode Latihan Lari Fartlek dan Circuit Training Terhadap Peningkatan Vo2Max UKM Futsal UPI Sumedang - Septiawan, Bahtiar Dwi Adi; Susilawati, Dewi; Lengkana, Anggi Setia (Jurnal Porkes, 2025)
This research is motivated by the low vo2max value of UPI Sumedang Futsal UKM athletes and the lack of training methods to increase vo2max. The purpose of the study was to determine the effect of fartlek running training and circuit training on increasing vo2max. This research is a type of quantitative research with the approach used, namely pre-experiment. The design used is two-group pretest-posttest. The population in this study were athletes at UKM Futsal UPI Sumedang totaling 12 people, with age criteria of 18-19 years and male gender. Sampling was done with purposive sampling technique. In this study using data collection techniques in the form of a multistage fitness test (MFT). From the results obtained, descriptive statistics will be carried out in the form of normality test, homogeneity test, hypothesis test and r square test. The results of hypothesis testing with paired sample T-test showed a t value of 2.378 (sig 0.041 < 0.05) for fartlek running and 3.143 (sig 0.026 < 0.05) for circuit training. So it can be said that fartlek running and circuit training have a significant effect on increasing vo2max in UPI Sumedang Futsal UKM athletes. With an increase in vo2max of 45.23% and 46.05% respectively, which indicates that both methods have a significant effect, but circuit training has a greater impact.